Adaptation of Bacillus subtilis carbon core metabolism to simultaneous nutrient limitation and osmotic challenge: a multi‐omics perspective. (31st March 2014) - Kohlstedt, Michael; Sappa, Praveen K.; Meyer, Hanna; Maaß, Sandra; Zaprasis, Adrienne; Hoffmann, Tamara; Becker, Judith; Steil, Leif; Hecker, Michael; van Dijl, Jan Maarten; Lalk, Michael; Mäder, Ulrike; et al.
Summary The Gram‐positive bacterium Bacillus subtilis encounters nutrient limitations and osmotic stress in its natural soil ecosystem. To ensure survival and sustain growth, highly integrated adaptive responses are required. Here, we investigated the system‐wide response of B. subtilis to different, simultaneously imposed stresses. To address the anticipated complexity of the cellular response networks, we combined chemostat experiments under conditions of carbon limitation, salt stress and osmoprotection with multi‐omics analyses of the transcriptome, proteome, metabolome and fluxome. Surprisingly, the flux through central carbon and energy metabolism is very robust under all conditions studied. The key to achieve this robustness is the adjustment of the biocatalytic machinery to compensate for solvent‐induced impairment of enzymatic activities during osmotic stress. Specifically, increased production of several enzymes of central carbon metabolism compensates for their reduced activity in the presence of high salt. A major response of the cell during osmotic stress is the production of the compatible solute proline. This is achieved through the concerted adjustment of multiple reactions around the 2‐oxoglutarate node, which drives metabolism towards the proline precursor glutamate. The fine‐tuning of the transcriptional and metabolic networks involves functional modules that overarch the individual pathways.